HRM Challenges in the Age of Globalisation - Agarwal, Sugandha; Saif Al Qouyatahi, Khalid Mohammed (International Research Journal of Business Studies, 2017)
Globalization has caused blurred international boundaries. On one hand, there is an open market for companies to seek talent on the other hand for employees a wide array of choices to work with, all because of globalization. But such types of open and globalized market exposes the firms to the challenges occurring in the prominent field of human resource. This paper is an attempt in understanding and analyzing the challenges existing and affecting the functioning of HRM while a company operates on global platform. The major encounters and worries of HR team, and the responses that HR managers need to make to such challenges with their increasing responsibilities in the globalized environment, have also been discussed in this paper. This is a communication and cross sectional study based on descriptive arguments and analytical logic developed through the responses received from HR teams of companies belonging to different sectors. Effective leadership, managing diverse workforce, role of technology in HR functions like recruitment and selection, legal and political aspects, skill management, global mindset are some of the jostling issues encountered by human resource function in the retro of globalization.